A 3-dimensional stationary cascade gamma-ray coincidence imager. (5th November 2021) - Liu, Xiao; Liu, Hui; Cheng, Li; Wu, Jing; Bao, Tianwei; Yao, Rutao; Liu, Yaqiang
Abstract: Objective. For certain radionuclides that decay through emitting two or more gamma photons consecutively within a short time interval—called cascade gamma-rays, the location where a radiopharmaceutical molecule emits cascade gamma-rays can be identified through coincidence detection of the photons. If each cascade photon is detected through a collimation mechanism, the location of the molecule can be inferred from the intersection of the back-projections of the two photons. Approach. In this work, we report the design and evaluation of a three-dimensional stationary imager based on this concept for imaging distributions of cascade-emitting radionuclides in radiopharmaceutical therapy. The imager was composed of two gamma-ray cameras assembled in an L-shape. Both cameras were NaI(Tl) scintillator based, one with a multi-slit collimator, the other with a multi-pinhole collimator. The field of view (FOV) was 100 mm (∅) × 100 mm ( L ). Based on the unique characteristics of the cascade coincidence events, we used a direct back-projection algorithm to reconstruct point source images for assessing the imager's intrinsic spatial resolution and the standard maximum likelihood expectation maximization algorithm for reconstructing phantom images. Main results. We evaluated the performance of the imager in both simulated and prototype form with radionuclide 177 Lu (cascade photon emitter). On the simulated imager, the coincidence detection efficiency at the center of FOV was 3.85 × 10 −6, the spatial resolution was 7.0 mm. On the prototype imager, the corresponding values were 3.20 × 10 −6 and 6.7 mm, respectively. Simulated hot-rod and experimental cardiac phantom studies demonstrate the first three-dimensional cascade gamma coincidence imager is fully functional.